Frailty and Cardiovascular Diseases Research into an Elderly Population - Veronese, Nicola; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This book aims to clarify the potential association between frailty and cardiovascular disease in older people. Covering the biological as well as the clinical point of view, it allows researchers and clinicians to discover the significance of this topic. The contributions cover the most important aspects in the potential relationship between frailty and cardiovascular disease. In particular, authoritative authors in this field have clarified the definition and the epidemiology of frailty and cardiovascular disease in older people. A large part of the volume is dedicated to the biological mechanisms of frailty and cardiovascular disease, trying to find those in common between these two conditions. Since this book is dedicated to both researchers and clinicians, we have proposed some chapters to the importance of comprehensive geriatric assessment in the evaluation and treatment of cardiovascular diseases and frailty. In this regard, the importance of geriatric evaluation in cardiac surgery for older people is well covered. Finally, the importance of cardiac rehabilitation and physical exercise is summarized, being, actually, the most important treatments for both frailty and cardiovascular disease. Written by many well-known and widely published experts in their respective fields, this book will appeal to a wide readership such as researchers in the field and clinicians, especially suited in geriatric medicine and cardiology who, every day, face frail older patients. .
Preface -- Frailty: what is it?- Tools for assessing frailty in older people: general concepts -- Epidemiology of frailty in older people -- Epidemiology of cardiovascular diseases in the elderly -- The impact of frailty on the role of the classical cardiovascular risk factors -- Frailty as cardiovascular risk factor (and vice versa) -- Inflammation, frailty and cardiovascular disease -- Oxidative stress, frailty and cardiovascular disease: current evidence -- The importance of cellular senescence in frailty and cardiovascular diseases -- Comprehensive geriatric assessment in cardiovascular disease -- Frailty in cardiac surgery -- Physical exercise for frailty and cardiovascular disease -- Cardiac rehabilitation for frail older people -- Future perspectives.
Keywords: Geriatrics; Aging; Developmental biology; Geriatric nursing; Cardiology; Epidemiology; Geriatrics/Gerontology.; Biogerontology; Geriatric Care; Cardiology; Epidemiology